2020
DOI: 10.1080/01944363.2020.1760002
|View full text |Cite
|
Sign up to set email alerts
|

Speaking to the Future

Abstract: COVID-19 is at the front and center of planning discussion. An emergent phenomenon, it is too soon to make definitive conclusions about its longterm effects on the field, cities, and regions. However, in this editorial I reflect on how COVID-19 intersects with the Journal of the American Planning Association's (JAPA's) editorial work, content, and links to the profession. JAPA's editorial workplace already spans a wide geography, and a steady stream of recent articles have examined how planning can engage alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This study clarifies how urban density and crowding represent two related but different concepts in pandemic-resilient design and planning theory (Forsyth 2003(Forsyth , 2020Batty 2009) by identifying the specific effects of density and crowding on NYC's 2020 COVID-19 epidemic.…”
Section: How Do Urban Density and Crowding Affect Infection Rates?mentioning
confidence: 66%
See 1 more Smart Citation
“…This study clarifies how urban density and crowding represent two related but different concepts in pandemic-resilient design and planning theory (Forsyth 2003(Forsyth , 2020Batty 2009) by identifying the specific effects of density and crowding on NYC's 2020 COVID-19 epidemic.…”
Section: How Do Urban Density and Crowding Affect Infection Rates?mentioning
confidence: 66%
“…To consider pandemic resilience in future urban design practice, a deeper understanding of the spatial distribution of social inequalities and their impact on public health is needed. The current pandemic has brought health equity to the forefront of discussions in the design, planning, and science communities (Forsyth 2020;World Bank 2020), and the emerging urban data sets that record public health indicators and COVID-19 cases in a high spatial resolution provide a unique opportunity to understand and tackle this question.…”
Section: Urban Inequalitymentioning
confidence: 99%
“…Public hesitancy around COVID-19 vaccines, as commonly noted by previous studies, is a significant challenge for public health and regional management in the COVID-19 era and future pandemics (Forsyth 2020; Office of the Assistant Secretary for Planning and Evaluation 2021; Ziafati Bafarasat 2021). Adjusting for individual-level and state-level variables in addition to temporal effect, this study found that not all measures of social distancing affect individuals’ vaccination.…”
Section: Discussionmentioning
confidence: 92%